(untitled) (Proceedings of the International Conference on Education, 2025)
The International Baccalaureate Diploma Programme (IBDP) Computer Science curriculum poses various challenges in teaching computational thinking (programming) concepts. As learners are from a variety of backgrounds other than computer science, they fail to understand the abstract concepts. This research examines how the gamified platforms and simulation-based tools help learners gauge the programming concepts. Even though there are studies that show the usage of gamification in STEM education, it lacks application in the IBDP Computer Science. This study incorporates a single-group quasi-experimental design with a wide range of pre- and post-assessments. Various assessment methods were incorporated to balance by including quantitative and qualitative data. Based on the results, it is evident that there is a 46% increase in learners’ comprehension of the IBDP Computer Science programming concepts and a significant improvement in their engagement level. With the qualitative data gathered, it is confirmed that the gamified platforms and simulation-based tools are fun and engaging for learners throughout their learning journey. It also enhances 21st-century skills like problem-solving and critical thinking amongst learners. Teachers gain actionable recommendations for integrating gamified and simulation-based tools to improve engagement and conceptual understanding in programming.